Fetal-Perinatal Exposure to Bisphenol-A Affects Quality of Spermatozoa in Adulthood Mouse - Teresa Chioccarelli; Francesco Manfrevola; Marina Migliaccio; Lucia Altucci; Veronica Porreca; Silvia Fasano; Gilda Cobellis (International Journal of Endocrinology)
Bisphenol-A (BPA) is considered an endocrine disruptor with estrogenic activity. It is described as an environment-polluting industrial chemical whose adverse effects on the male reproductive system depend on the period of exposure (i.e., fetal, prepubertal, or adult life). We exposed male mice to BPA during the fetal-perinatal period (from 10 days post coitum to 31 days post partum) and investigated the impact of this early-life exposure on gamete health in adulthood animals at 78 days of age. Both in control and BPA-exposed mice, viability and motility of spermatozoa, as well as sperm motility acquisition and chromatin condensation of spermatozoa, have been evaluated. Results reveal harmful effect of BPA on viability and motility of sperm cells as well as on chromatin condensation status during epididymal maturation of spermatozoa. In particular, BPA exposure interferes with biochemical mechanism useful to stabilize sperm chromatin condensation, as it interferes with oxidation of thiol groups associated to chromatin.